2020
DOI: 10.1038/s41598-020-66588-4
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of TSC1 and TSC2 in Danish patients with tuberous sclerosis complex

Abstract: tuberous sclerosis complex (tSc) is an autosomal dominant disorder characterized by hamartomas in the skin and other organs, including brain, heart, lung, kidney and bones. tSc is caused by mutations in TSC1 and TSC2. Here, we present the TSC1 and TSC2 variants identified in 168 Danish individuals out of a cohort of 327 individuals suspected of TSC. A total of 137 predicted pathogenic or likely pathogenic variants were identified: 33 different TSC1 variants in 42 patients, and 104 different TSC2 variants in 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 39 publications
3
15
1
Order By: Relevance
“…Additionally, we found that 29% TSC1 variants were familial variants, whereas only 9% TSC2 variants were inherited from families, which is consistent with the results of the previous studies [ 15 , 21 , 22 ]. We confirmed the higher frequency of familial TSC1 variants compared to that of familial TSC2 variants, which is attributed to the smaller size and simpler structure of the TSC1 genomic locus, and the rarity of missense mutations, frames shift mutations and large rearrangements at the locus [ 12 ]. A large number of TSC1 variants was observed in familial cases probably because patients with TSC1 variants are less likely to be affected by severe neurocognitive impairment and are therefore more likely to have offspring [ 13 , 23 ].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Additionally, we found that 29% TSC1 variants were familial variants, whereas only 9% TSC2 variants were inherited from families, which is consistent with the results of the previous studies [ 15 , 21 , 22 ]. We confirmed the higher frequency of familial TSC1 variants compared to that of familial TSC2 variants, which is attributed to the smaller size and simpler structure of the TSC1 genomic locus, and the rarity of missense mutations, frames shift mutations and large rearrangements at the locus [ 12 ]. A large number of TSC1 variants was observed in familial cases probably because patients with TSC1 variants are less likely to be affected by severe neurocognitive impairment and are therefore more likely to have offspring [ 13 , 23 ].…”
Section: Discussionsupporting
confidence: 63%
“…In this study, we identified 161 variants in 173 unrelated patients (93%), including 27 (16%) with TSC1 variants and 134 (77%) with TSC2 variants, which is higher than that reported in other countries [ 12 15 ]. This is due to the NGS applied in this study.…”
Section: Discussioncontrasting
confidence: 52%
“…Germline heterozygous mutations in TSC1 are known to be responsible for hamartoma syndromes, including tuberous sclerosis (TS) that confer increased susceptibility to renal cancer [ 64 ]. Of note, the TSC1 variants observed in our series were located in exons 17 and 18, encoding part of the tuberin-binding region regularly targeted in TS [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…This particular TSC2 mutation (c.5238_5255del, p. (His1746_Arg1751del of 6 amino acids in exon 41) has been frequently reported. In fact, in multiple studies profiling mutations in patients with TSC throughout the world, this same 6 amino acids deletion was found to be the most common mutation (Dabora et al ., 2001; Jones et al, 1999; Reyna-Fabián et al, 2020; Rosengren et al, 2020; Wang et al, 2013). The impact from this specific mutant microdeletion allele thus has important consequences for patients with TSC globally.…”
Section: Discussionmentioning
confidence: 99%